Carbon nanotubes - Characteristic of the substance, biological effects and occupational exposure levels - Anna Maria Świdwińska-Gajewska; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2017)
Carbon nanotubes (CNTs) are a diverse group of nano-objects in terms of structure, size (length, diameter), shape and characteristics. The growing interest in these structures is due to the increasing number of people working in exposure to CNTs. Occupational exposure to carbon nanotubes may occur in research laboratories, as well as in plants producing CNTs and their nanocomposites. Carbon nanotubes concentration at the emission source may reach 107 particles/cm3. These values, however, are considerably reduced after the application of adequate ventilation. Animal studies suggest that the main route of exposure is inhalation. Carbon nanotubes administered orally are largely excreted in the feces. In animals exposed by inhalation, CNTs caused mainly inflammation, as a result of oxidative stress, leading above all to changes in the lungs. The main effect of animal dermal exposure is oxidative stress causing local inflammation. In animals exposed by ingestion the mild or no toxicity was observed. Carbon nanotubes did not induce mutations in the bacterial tests, but they were genotoxic in a series of tests on cells in vitro, as well as in exposed mice in vivo. Embryotoxicity of nanotubes depends mainly on their modifications and carcinogenicity - primarily on the CNT size and its rigidity. Occupational exposure limits for CNTs proposed by world experts fall within the range of 1-80 μg/m3. The different effects of various kinds of CNT, leads to the conclusion that each type of nanotube should be treated as a separate substance with individual estimation of hygienic normative. Med Pr 2017;68(2):259-276